Reception of the stethoscope and Laënnec's book. - Bishop, P J (Thorax, 1981)
A study of contemporary book reviews and other notices enables us to trace the reception of the stethoscope and Laënnec's book between 1816 and 1826. It is quite clear from these that the stethoscope was welcomed with enthusiasm by most people who saw it as the first major diagnostic tool medicine had ever had. Laënnec's book was recognised as being the most important, interesting, accurate, and complete work on diseases of the chest that had ever been published.